Adopted “mammoths” from Alaska turn out to be a whale's tale - Matthew J. Wooller; Pat Drukenmiller; Gonzalo Oteo‐García; Francesca Di Paolo; Love Dalén; Nick Baker; Nancy Bigelow; Stormy Fields; Sambit Ghosh; Kathryn E. Krasinski; Ben Lamm; Alistair J. Monteath; et al. (Journal of Quaternary Science, 2026)
Radiocarbon‐dated fossils indicate woolly mammoths were extirpated from mainland Beringia around 13 000 years ago. However, environmental DNA in permafrost suggests small “cryptic“ populations survived into the Holocene. Resolving this discrepancy is crucial to understanding the drivers of mammoth extinction. The Adopt‐a‐Mammoth project, launched in 2022, is increasing the number of radiocarbon‐dated mammoth fossils to locate the chronologically youngest specimens. Here, we report results from two “mammoth“ vertebral epiphyseal plates from interior Alaska that produced the youngest radiocarbon ages associated with mammoth specimens (~1900–2700 cal a BP). However, isotopic data indicated that these individuals consumed marine resources, and subsequent ancient DNA analysis revealed the specimens were in fact from a North Pacific Right whale and a Minke whale. Solving the mystery of recent “mammoth” fossils raised new questions. How did the remains of ancient whales become emplaced in sediment so far from the coastline? We briefly consider four scenarios to account for this.

Strong Bottlenecks Constrain Adaptive Coevolution in a Host–Parasite Metapopulation - Pascal Angst; Christoph R. Haag; Frida Ben‐Ami; Peter D. Fields; Dieter Ebert (Molecular Ecology, 2025)
Although parasites are well‐known for adaptively evolving in order to exploit their hosts, they may experience strong genetic drift during transmission bottlenecks when infecting a new host. Host population structure and host population bottlenecks can also lead to genetic drift effects in parasite populations, constraining their adaptive evolution further. Here, we investigate the role of host population structure on the evolution of the microsporidian parasite Hamiltosporidium tvaerminnensis in a dynamic metapopulation of its microcrustacean host Daphnia magna . In following whole‐genome allele frequencies of 59 host and parasite subpopulations for up to 10 years, we found that both antagonists showed patterns of co‐dispersal and isolation‐by‐distance, but allele frequencies were much more dynamic in the host, where we found signatures of recurrent genetic bottlenecks. In the parasite, we observed high levels of shared heterozygosity among subpopulations but also subpopulation‐specific runs of homozygosity (ROHs). We hypothesise that deleterious ROHs, which originate from loss of heterozygosity events during asexual recombination, are fixed in subpopulations following host‐mediated parasite population bottlenecks when host and parasite co‐disperse into a habitat patch where the parasite is not yet present. Thus, host population structure and metapopulation dynamics leave a clearly traceable genomic signature in the coevolving parasite. Contrary to the prevailing assumption that parasites evolve at higher rates than their hosts, our study not only suggests that parasites can evolve more slowly than their host, but also that host dynamics can accelerate drift processes in the parasite.

Guanosine tetraphosphate (ppGpp) is a new player in Brassica napus L. seed development - Sena Turkan; Milena Kulasek; Agnieszka Zienkiewicz; Agnieszka Mierek-Adamska; Edyta Skrzypek; Marzena Warchoł; Aleksandra Szydłowska-Czerniak; Julia Bartoli; Ben Field; Grażyna B. Dąbrowska (Food Chemistry, 2024)

PlantACT! – how to tackle the climate crisis - Heribert Hirt; Salim Al-Babili; Marilia Almeida-Trapp; Antoine Martin; Manuel Aranda; Dorothea Bartels; Malcolm Bennett; Ikram Blilou; Damian Boer; Alix Boulouis; Chris Bowler; Sophie Brunel-Muguet; et al. (Trends in Plant Science, 2023)

Aquatic macrophytes show distinct spatial trends in contaminant metal and nutrient concentrations in Coeur d’Alene Lake, USA - Ben D. Scofield; Scott F. Fields; Dale W. Chess (Environmental Science and Pollution Research, 2023)

Applying genetic technologies to combat infectious diseases in aquaculture - Nicholas A. Robinson; Diego Robledo; Lene Sveen; Rose Ruiz Daniels; Aleksei Krasnov; Andrew Coates; Ye Hwa Jin; Luke T. Barrett; Marie Lillehammer; Anne H. Kettunen; Ben L. Phillips; Tim Dempster; et al. (Reviews in Aquaculture, 2023)
Disease and parasitism cause major welfare, environmental and economic concerns for global aquaculture. In this review, we examine the status and potential of technologies that exploit genetic variation in host resistance to tackle this problem. We argue that there is an urgent need to improve understanding of the genetic mechanisms involved, leading to the development of tools that can be applied to boost host resistance and reduce the disease burden. We draw on two pressing global disease problems as case studies—sea lice infestations in salmonids and white spot syndrome in shrimp. We review how the latest genetic technologies can be capitalised upon to determine the mechanisms underlying inter‐ and intra‐species variation in pathogen/parasite resistance, and how the derived knowledge could be applied to boost disease resistance using selective breeding, gene editing and/or with targeted feed treatments and vaccines. Gene editing brings novel opportunities, but also implementation and dissemination challenges, and necessitates new protocols to integrate the technology into aquaculture breeding programmes. There is also an ongoing need to minimise risks of disease agents evolving to overcome genetic improvements to host resistance, and insights from epidemiological and evolutionary models of pathogen infestation in wild and cultured host populations are explored. Ethical issues around the different approaches for achieving genetic resistance are discussed. Application of genetic technologies and approaches has potential to improve fundamental knowledge of mechanisms affecting genetic resistance and provide effective pathways for implementation that could lead to more resistant aquaculture stocks, transforming global aquaculture.

Contaminant metal concentrations in three species of aquatic macrophytes from the Coeur d’Alene Lake basin, USA - Ben D. Scofield; Kathleen Torso; Scott F. Fields; Dale W. Chess (Environmental Monitoring and Assessment, 2021)

sPlotOpen – An environmentally balanced, open‐access, global dataset of vegetation plots - Francesco Maria Sabatini; Jonathan Lenoir; Tarek Hattab; Elise Aimee Arnst; Milan Chytrý; Jürgen Dengler; Patrice De Ruffray; Stephan M. Hennekens; Ute Jandt; Florian Jansen; Borja Jiménez‐Alfaro; Jens Kattge; et al. (Global Ecology and Biogeography, 2021)
Motivation Assessing biodiversity status and trends in plant communities is critical for understanding, quantifying and predicting the effects of global change on ecosystems. Vegetation plots record the occurrence or abundance of all plant species co‐occurring within delimited local areas. This allows species absences to be inferred, information seldom provided by existing global plant datasets. Although many vegetation plots have been recorded, most are not available to the global research community. A recent initiative, called ‘sPlot’, compiled the first global vegetation plot database, and continues to grow and curate it. The sPlot database, however, is extremely unbalanced spatially and environmentally, and is not open‐access. Here, we address both these issues by (a) resampling the vegetation plots using several environmental variables as sampling strata and (b) securing permission from data holders of 105 local‐to‐regional datasets to openly release data. We thus present sPlotOpen, the largest open‐access dataset of vegetation plots ever released. sPlotOpen can be used to explore global diversity at the plant community level, as ground truth data in remote sensing applications, or as a baseline for biodiversity monitoring. Main types of variable contained Vegetation plots ( n = 95,104) recording cover or abundance of naturally co‐occurring vascular plant species within delimited areas. sPlotOpen contains three partially overlapping resampled datasets ( c . 50,000 plots each), to be used as replicates in global analyses. Besides geographical location, date, plot size, biome, elevation, slope, aspect, vegetation type, naturalness, coverage of various vegetation layers, and source dataset, plot‐level data also include community‐weighted means and variances of 18 plant functional traits from the TRY Plant Trait Database. Spatial location and grain Global, 0.01–40,000 m². Time period and grain 1888–2015, recording dates. Major taxa and level of measurement 42,677 vascular plant taxa, plot‐level records. Software format Three main matrices (.csv), relationally linked.

Growth of bultfonteinite and hydrogarnet in metasomatized basalt xenoliths in the B/K9 kimberlite, Damtshaa, Botswana: insights into hydrothermal metamorphism in kimberlite pipes - Ben Buse; John C. Schumacher; R. Stephen J. Sparks; Matthew Field (Contributions to Mineralogy and Petrology, 2010)

The salinity tolerance of freshwater macroinvertebrate eggs and hatchlings in comparison to their older life-stages: a diversity of responses - Ben J. Kefford; Dayanthi Nugegoda; Liliana Zalizniak; Elizabeth J. Fields; Kathryn L. Hassell (Aquatic Ecology, 2007)

Expression of a Brassica Isopropylmalate Synthase Gene in Arabidopsis Perturbs Both Glucosinolate and Amino Acid Metabolism - Ben Field; Caroline Furniss; Andrew Wilkinson; Richard Mithen (Plant Molecular Biology, 2006)